A framework for understanding energy for water. Issue 3 (3rd May 2016) - Napoli, Christopher; Garcia-Tellez, Berenice
Abstract: This article offers a framework for understanding how energy is used to meet water demand in countries. Specifically, the relationships between energy use and water scarcity, the location of renewable water resources, and aggregate water demand are explored. The article also examines how policy options such as water price reforms, agriculture subsidies and crop elimination may influence the energy use and energy intensity of water withdrawals. Conclusions suggest that while policy options exist, certain uncontrollable factors such as severe water scarcity or substantial freshwater abundance limit the ability of some countries to significantly improve the aggregate energy efficiency of water provision.